2008
DOI: 10.1128/aac.01159-07
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Antifungal Activities of T-2307, a Novel Arylamidine

Abstract: The in vitro and in vivo antifungal activities of T-2307, a novel arylamidine, were evaluated and compared with those of fluconazole, voriconazole, micafungin, and amphotericin B. T-2307 exhibited broad-spectrum activity against clinically significant pathogens, including Candida species (MIC range, 0.00025 to 0.0078 g/ml), Cryptococcus neoformans (MIC range, 0.0039 to 0.0625 g/ml), and Aspergillus species (MIC range, 0.0156 to 4 g/ml). Furthermore, T-2307 exhibited potent activity against fluconazole-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
80
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 28 publications
7
80
0
2
Order By: Relevance
“…1) that is structurally similar to a class of aromatic diamidines that includes pentamidine (6). This investigational agent has been shown to have potent in vitro activity against Candida species and Cryptococcus neoformans (6) and works by causing the collapse of fungal mitochondrial membrane potential (7). Our preliminary data also suggest that T-2307 maintains in vitro potency against echinocandin-resistant C. albicans and Candida glabrata isolates (8).…”
supporting
confidence: 55%
See 2 more Smart Citations
“…1) that is structurally similar to a class of aromatic diamidines that includes pentamidine (6). This investigational agent has been shown to have potent in vitro activity against Candida species and Cryptococcus neoformans (6) and works by causing the collapse of fungal mitochondrial membrane potential (7). Our preliminary data also suggest that T-2307 maintains in vitro potency against echinocandin-resistant C. albicans and Candida glabrata isolates (8).…”
supporting
confidence: 55%
“…Our preliminary data also suggest that T-2307 maintains in vitro potency against echinocandin-resistant C. albicans and Candida glabrata isolates (8). In addition, previous studies have also demonstrated in vivo efficacy in murine models of invasive candidiasis, systemic cryptococcosis, and disseminated aspergillosis (6,9). Our objective was to evaluate the in vitro activity of T-2307 against echinocandin-resistant C. albicans and determine its efficacy against experimental invasive candidiasis caused by a resistant and virulent strain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1A) is a novel arylamidine and is now undergoing clinical trials. We have previously reported that T-2307 had broad-spectrum potent in vitro and in vivo activities against the majority of fungal pathogens, including Candida albicans, Aspergillus fumigatus, and Cryptococcus neoformans, which is not susceptible to candins (17). T-2307 exhibits excellent antifungal activity against fluconazole-resistant Candida spp.…”
mentioning
confidence: 99%
“…We had previously reported that T-2307, a novel arylamidine, exhibits broad-spectrum in vitro and in vivo antifungal activity against clinically significant pathogens (7,8,16). The analogous arylamidine derivatives, such as pentamidine and DB75, exhibit antiprotozoan activities against Plasmodium, Trypanosoma, and Leishmania (2,3,14).…”
mentioning
confidence: 99%